Uso do método de custeio direto na produção de leite no semiárido sergipano - Freitas, José Leoncio Delmondes Pereira (2019)
The objective of this study was to compare the direct costing methods, operating cost and total cost, to determine the costs of milk factories located in Sergipano Semiárido, The research comprised the period from April 2018 to March 2019, considered in this research as a production cycle. Data collection it was carried out in 30 dairy farms, with mechanical milking and the main source of income of the producer, in two municipalities, through interviews with the producer. For purposes of comparison, amounts receivable and/or payable and inventories were disregarded at the beginning and end of the production cycle, which is why there was no difference in cost component values between the different methods evaluated. The same chart of accounts was used for all methods and indicators according to each method evaluated. In the direct costing and total cost methods we considered fixed and variable costs and in the operating cost method, the costs were classified as effective operating cost and other costs. Regarding profitability indicators, in the direct costing method, contribution margin, earnings before interest taxes, depreciation and amortization - EBITDA and net result. The total cost method considered net income and the operating cost method considered gross margin, net margin and net income. Although operating cost and total cost methods are more accessible to producers, the direct costing method, since it admits only the costs actually incurred in the production cycle.